Psychological Consequences of Social Isolation During COVID-19 Outbreak - Pietrabissa, Giada; Simpson, Susan G. (Frontiers in Psychology, 2020)
Perceived social isolation during the COVID-19 pandemic has significantly resulted in a large number of psychological consequences. Changes in our daily lives, feeling of loneliness, job loss, financial difficulty and grief over the death of loved ones has the potential to affect the mental of many. In an atmosphere of uncertainty, it is essential that clear and precise information is offered on the problem. In this contribution, reasons and need for a rapid response to the mental health impacts of COVID-19 are highlighted. Moreover, suggestions for individuals to regulate their emotions effectively and appropriately are provided.